2015
DOI: 10.1021/acs.jpcb.5b08446
|View full text |Cite
|
Sign up to set email alerts
|

Silanol-Assisted Carbinolamine Formation in an Amine-Functionalized Mesoporous Silica Surface: Theoretical Investigation by Fragmentation Methods

Abstract: The aldol reaction catalyzed by an amine-substituted mesoporous silica nanoparticle (amine-MSN) surface was investigated using a large molecular cluster model (Si392O958C6NH361) combined with the surface integrated molecular orbital/molecular mechanics (SIMOMM) and fragment molecular orbital (FMO) methods. Three distinct pathways for the carbinolamine formation, the first step of the amine-catalyzed aldol reaction, are proposed and investigated in order to elucidate the role of the silanol environment on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Finally, consider an application of the Haswell and KNL architectures to a transition state problem: a model catalytic system studied by de Lima Batista et al As illustrated in Figure , the model reaction begins with two reactants (acetone, propylamine) plus the model catalyst silanol, moves to a transition state, and ends with the product carbinolamine and the catalyst silanol. All geometries were optimized using MP2/6-31G+(d,p); the transition state was verified by an MP2 Hessian.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, consider an application of the Haswell and KNL architectures to a transition state problem: a model catalytic system studied by de Lima Batista et al As illustrated in Figure , the model reaction begins with two reactants (acetone, propylamine) plus the model catalyst silanol, moves to a transition state, and ends with the product carbinolamine and the catalyst silanol. All geometries were optimized using MP2/6-31G+(d,p); the transition state was verified by an MP2 Hessian.…”
Section: Resultsmentioning
confidence: 99%
“…Particle designs could include the following. (i) Use of a particle system with variable tumbling rates to enhance surface radical diffusion and facilitate transiting off of volatile radicals, in particular given the importance of volatile alkoxy radicals as reactive intermediates in atmospheric chemistry. − (ii) An alkoxy radical surface migration system can be studied experimentally based on surface silanols with increasing water content to assess the effects on the radical migration distance. − Simulations of alkoxy radical surface migration can also be studied by silica cluster models with quantum mechanics/molecular mechanics methods . (iii) A complementary SPR/EPR method can be developed for product distribution by radical recombination and assist in distinguishing between stationary and migratory surface radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking demonstrated that GSSA binds to SCARB1 receptors with −5.7 kcal/mol and very high geometric matching. In comparison, carbinoil stabilizes SCARB1 at −3.2 kcal/mol [48] and the LDL-derived pyrene-sphingomyelin binding energy was 7.1 Âą 0.9 Kcal/mol [49]. SCARB1 receptors have been well described as a high-density lipoprotein receptor which mediates both the selective uptake of cholesterol esters and the efflux of cholesterol.…”
Section: Discussionmentioning
confidence: 99%